Most running demand passages of match play in youth soccer congestion period - Castellano, J.; Martin-Garcia, A.; Casamichana, D. (Biology of Sport, 2020)
The objective of this study was to determine whether there is a decrease in the physical performance of the players in the most demanding passages (MDP) during periods of competition congestion. The study involved 15 under-19 players, belonging to a club in Spain`s first division (age: 18.1 ± 0.8 years, weight: 70.2 ± 4.9 kg and height: 1.78 ± 0.06 m), who were monitored during 23 national and international official matches in the 2018/19 season. The Youth League matches were played between two matches in the national championship in six different weeks. The league matches corresponded to the first 17 matches of the league championship, the period in which the 6 matches in the Youth League were played. The two physical variables analysed were total distance (TD) and distance at > 21 km·h-1 (TD21). Using the rolling average, four time windows were taken (1, 3, 5 and 10 min), and the values were relativized to the minute (m·min-1). The main results were that: there were more MDP in the first halves than in the second halves of all the time windows; 2) the central match in the week (Youth League) was the most demanding one; and 3) the players maintained the TD and TD21 in the MDP in the third match compared to the first. The results of this study could provide trainers with information on the need to design training tasks that simulate the demands of competition in relation to the TD and the TD21 according to different time windows.